Development of a portable blood salvage and autotransfusion technology to enhance survivability of personnel requiring major medical interventions in austere or military environments. Issue 2 (26th October 2017) - Gourlay, Terence; Simpson, C; Robertson, C A
Abstract : Introduction: Uncontrolled haemorrhage is the leading cause of death on the battlefield, and two-thirds of these deaths result from non-compressible haemorrhage. Blood salvage and autotransfusion represent an alternative to conventional blood transfusion techniques for austere environments, potentially providing blood to the casualty at point of injury. The aim of this paper is to describe the design, development and initial proof-of-concept testing of a portable blood salvage and autotransfusion technology to enhance survivability of personnel requiring major medical interventions in austere or military environments. Method: A manually operable, dual-headed pump was developed that removes blood from site of injury to a collection reservoir (upper pump) and back to casualty (lower pump). Theoretical flow rate calculations determined pump configuration and a three-dimensionally printed peristaltic pump was manufactured. Flow rates were tested with fresh bovine blood under laboratory conditions representative of the predicted clinical environment. Results: Mathematical modelling suggested flow rates of 3.6 L/min and 0.57 L/min for upper and lower pumps. Using fresh bovine blood, flow rates produced were 2.67 L/min and 0.43 L/min. To mimic expected battlefield conditions, upper suction pump flow rate was calculated using a blood/air mixture. Conclusion: The authors believe that this technology can potentially enhance survivability for casualties in austere and deployed military settings through autotransfusion and cell concentration. It reduces negative effects of blood donation on the conventional donor pool, and potentially negates the logistical constraints associated with allogenic transfusions.